Is Financial Capital Globalization the Necessity of Historical Development - Zhihua, E (Journal of Finance, 2000)
As an integral part of financial globalization,the globalization of capital flows is influenced by business cycle and trade factors,international interest rate adjustments,capital account management policies,the development of the international monetary system,as well as other factors such as the policy intentions of multinational corporations and relevant international organizations.And it results from the combination of the objective certainties of historical development and the man made driving forces by relevant countries or organizationsThe globalization development process of capital flows is characterized with unprecedented complexity,while the distribution of its benefits is possessed of obvious inequality.However,the complexity and inequality will not influence the objective sustainability of capital globalization development.